Tocilizumab therapy for persistent high-grade fever in systemic lupus erythematosus: two cases and a literature review. Issue 3 (March 2022) - Chaoyi, Ma; Shrestha, Bikash; Hui, Li; Qiujin, Ding; Ping, Fu
Tocilizumab (TCZ) is a humanized immunoglobulin (Ig) G1 monoclonal antibody directed against the interleukin (IL)-6 receptor. We report on two patients with persistent high-grade fever and systemic lupus erythematosus (SLE) who were treated with TCZ. Two female Chinese patients presented with SLE and high-grade fever, with raised inflammatory markers including C-reactive protein, erythrocyte sedimentation rate, and IL-6, but no signs of opportunistic infections. Their fever and other symptoms responded poorly to broad-spectrum antibiotics, antifungals, antivirals, and glucocorticoids. They were both treated with TCZ. Their body temperatures returned to normal after treatment with TCZ, and other symptoms, including arthralgia, gradually improved. Both patients were followed-up and their conditions remained steady to date. TCZ may thus be an alternative treatment for patients with SLE and persistent high-grade fever who fail to respond to initial antibiotics and high-dose glucocorticoids.